Reforma do ensino médio sob a lei nº 13.415/2017: que formação para a classe trabalhadora? - Alves, Elaine Gonçalves (2022)
Research in the Brazilian educational field is consensual as to the perception that high school, the final stage of basic education according to the Law of Directives and Bases of National Education nº 9.394 of December 20, 1996, is a phase that raises debates and reflections due to persistent obstacles to access, permanence and type of training offered to young people. This study started from the problem on the training that is being offered to young Brazilians, especially those from the working class, with the high school reform expressed in Law nº 13.415/2017. It also questions the effectiveness of students’ “choice” for training itineraries and defends the thesis that this reform is a mechanism that will intensify school dualism and deepen inequalities and educational opportunities for young Brazilians by offering a precarious and limited education. The general objective of this study was to analyze the determinants of Law nº 13.415/2017 considering the historical context and possible consequences of this regulation. For this, we used the method of historical-dialectical materialism considered relevant to interpret and analyze reality in a critical-reflexive way and understand the contradictions intersecting with the historical-political-economic and cultural determinations. Documentary and bibliographic research related to the theme was used, presenting what is contained in the documents - laws, resolutions, decrees, ordinances, among others - and in the academic productions carried out on High School. The vertex of this study was the critical analysis of Law nº 13.415/2017 using Content Analysis as a methodological instrument (BARDIN, 2002) based on the following categories: Time spent at school (hour load of the course and Full-Time High School - FTHS); Curricular reorganization (BNCC + Training Itineraries); Duality of teaching and Inequality. It was found that the proposition of a “new” high school by Law nº 13.415/2017 is not real; at other moments in history, equivalent organization, guidelines, in short, approximations between the normative devices were observed – the latter express the ideology that permeates the capitalist society whose relations divide the objectives for the dominant class and the subaltern class. The study showed that this reform will increase educational inequalities and provide young working-class children with a precarious and superficial education; it will be an empty process of knowledge construction. It was concluded that this is another reform implemented in high school whose intention is to meet the capitalist demand by offering professional training, orchestrated to make young people enter the job market.